2021
DOI: 10.5114/fmpcr.2021.103184
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and caregiver’s burden in patients with chronic diseases: a cross-sectional study

Abstract: Background. Cancer and type 2 diabetes (T2D), as two groups of prevalent chronic diseases, are associated with different social, economic and emotional consequences, and they can change the quality of life (QoL) of their caregivers. Objectives. The aim of the present study was to determine the relationship between QoL and the burden on caregivers of patients with cancer and T2D. Material and methods. This comparative cross-sectional study was conducted on 308 caregivers of patients with cancer and T2D. Data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…This resulted in a decline in their health and quality of life (Zou, 2014). Similar to the current study's findings, the findings of a study done by (Mirhosseini et al, 2021) in Turkey aiming at assessing the QoL of family caregivers of cancer patients revealed that caregivers with chronic conditions reported lower QoL.…”
Section: Discussionsupporting
confidence: 89%
“…This resulted in a decline in their health and quality of life (Zou, 2014). Similar to the current study's findings, the findings of a study done by (Mirhosseini et al, 2021) in Turkey aiming at assessing the QoL of family caregivers of cancer patients revealed that caregivers with chronic conditions reported lower QoL.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study showed that caregiver’s educational level inversely correlated with the caring burden level. 21 Our study showed that half of the caregivers have a college degree and report a low income. This is similar to the findings of another recent study.…”
Section: Discussionmentioning
confidence: 57%
“…The Novak and Guest’s Caregiver Burden Inventory (CBI) was used to examine the caregiver care burden, which has been used in the context of chronic diseases [ 37 ]. This questionnaire contains 24 items and five dimensions, which include time dependence care burden (5 items), developmental care burden (5 items), physical care burden (4 items), social care burden (5 items), and emotional care burden (5 items).…”
Section: Methodsmentioning
confidence: 99%